Functions Modeling Change: A Preparation for Calculus, 5th Edition

Published by Wiley
ISBN 10: 1118583191
ISBN 13: 978-1-11858-319-7

Chapter 5 - Logarithmic Functions - Exercises to Skills for Chapter 5 - Page 232: 6



Work Step by Step

First, use the fact that $e^{\ln a}=a$ to simplify the expression to $e^{\ln3}-\ln e=3-\ln e$. Next, use the fact that $e=e^1$ and $\ln e^a=a$ to simplify $\ln e$ to $\ln e=\ln e^1=1$. Thus, $$e^{\ln 3}-\ln e=3-1=2$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.